PEMBENTUKAN LIMBAH DAUR ULANG PLASTIK HDPE MENJADI GITAR AKUSTIK: FORMING HDPE PLASTIC RECYCLING WASTE INTRO AN ACOUSTIC GUITAR - Naufal Fajar Gumelar; Muhammad Ihsan (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Forming Hdpe Plastic Recycling Waste Intro An Acoustic Guitar. This study aims to explore the potential of recycled High-Density Polyethylene (HDPE) as an alternative material for acoustic guitar construction. Using an experimental approach, HDPE waste was collected, cleaned, shredded, and melted using a hot press machine at 155°C for 80 minutes to form 5 mm thick boards. These boards were then cut and shaped according to the national acoustic guitar design standard (SNI), incorporating an X-bracing structure to maintain structural strength and sound resonance. The guitar body was formed by a professional luthier using conventional tools and techniques. The results show that HDPE can be shaped into an acoustic guitar body with a structure resembling that of standard wooden guitars. Although acoustic performance has not yet been tested, this study demonstrates the potential of HDPE as a viable material for acoustic guitar bodies and supports innovation in musical instrument design. Further research is recommended to evaluate the sound quality and durability of the instrument comprehensively.